The buried king and the memory of the future: From Washington Irving to Bruce Springsteen. (June 2020) - Portelli, Alessandro
Drawing from stories, literary texts, myths, and songs, the article explores the "intangible" imagery—dreams, souls, ghosts, memory—that uses the nostalgia of the past to announce the possibility of a future. The image of the buried and sleeping king represents myth of a past Golden Age but also the vision of a future rebirth. Such examples include the figures of Rip Van Winkle, Hendrick Hudson, and Boabdil in the works of US author Washington Irving (1783–1859). Other examples include the figure of Metacomet, also rescued by Irving, or of Atahualpa, of Inca mythology. From Washington Irving to the songs of Bruce Springsteen, the image of a past that accompanies and haunts the present to project a utopian future never ceases to reappear.